Constipation in Children: An Example of A Conflict Situation - Derya Altay (Galenos Publishing House, 2023)
Constipation is a prevalent issue in the pediatric population and is predominantly of functional origin. It often presents with symptoms such as abdominal pain, vomiting, and anorexia, making it a significant complaint among young patients. A comprehensive patient history and physical examination are typically sufficient for the diagnosis of functional constipation. Early intervention and patient and parent education are crucial for the success of treatment, which involves dietary adjustments, toilet training, and medical interventions. This review outlines an approach to managing constipation in children.